Promotion - Alam, Hasan B. (Clinics in Colon and Rectal Surgery, 2013)
This article gives an overview of the promotion process in an academic medical center. A description of different promotional tracks, tenure and endowed chairs, and the process of submitting an application is provided. Finally, some practical advice about developing skills and attributes that can help with academic growth and promotion is dispensed.
Keywords: promotion; tenure; writing; time management; academic